Bureaucratising Islam: State strategies and Muslim responses in Singapore. Issue 3 (2nd September 2018) - Abdullah, Walid Jumblatt
ABSTRACT: Southeast Asian countries have, since independence, grappled with the issue of religious management. Many of them, especially in the Malay Archipelago, have attempted to bureaucratize Islam specifically, as they attempt to keep religion in check and/or harness it for political and nation-building purposes. This paper investigates how the state in Singapore has drawn the boundaries for Islam's involvement in public affairs via this bureaucratisation. The attempt by the state to be the ultimate arbiter in Islamic affairs is primarily successful, though it is not without contestations. Due to the constricting nature of the political system, Muslim actors have largely tried to maximise their influence within the confines of what the state deems permissible either by not confronting the state directly or by overtly cooperating with it in some instances. Dissent towards the state-sanctioned version of Islam may arise in pockets, especially on social media, but it is limited both in scope and participation.